Overview of Coral Morphology and Plasticity Research Using Bibliometric Methods - Ridha Alamsyah; Neviaty P. Zamani; Dietriech G. Bengen; I Wayan Nurjaya; Derek Soto (Marine Science Department Diponegoro University, 2022)
One of the determining variables that influences coral growth morphology is the aquatic environment. Reef corals are unusual organisms with plant-like development patterns. Reef growth is influenced greatly by the aquatic environment, particularly hydro-oceanography. The same type of coral can have different morphological forms. This mismatch in form can lead to type identification mistakes. There is still a lack of research on morphological changes as an impact of coral plasticity in responding to environmental variables. The goal of this work is to compile a bibliography of coral morphological plasticity studies. Publish or Perish (PoP) program locates the Scopus database and processes the articles. After screening, 101 of the 138 articles found in the Scopus database are eligible to be found. Mendeley reference manager software is then used to handle the selected references. After maintaining the database, use VOSviewer software to classify and visualize the data. The findings suggest that the research topic was chosen based on keywords. Coral morphological plasticity research is primarily focused on the terms coral colonies and species. Small-scale coral morphology, morphological variability, and coral morphometrics are among the topics that have received little attention. The possibility of conducting research on the three subjects is still open. There are still many unanswered mysteries about coral. This work is crucial to research since it illustrates the direction of future plans for exposed coral morphology and plasticity. This review serves as a useful starting point for future coral morphology and plasticity research.